Does industry-university-research cooperation promote the environmental efficiency of China’s high-tech manufacturing? - Peng, Feng; Zhang, Xichun (Frontiers in Ecology and Evolution, 2023)
As one of the important strategic measures to increase the international competitiveness of high-tech manufacturing (HTM), industry-university-research cooperation (IURC) has received increasing attention in China. However, there is little literature to explore the links between IURC and the environmental efficiency (EE) of HTM. To incorporate a variety of environmental pollution indicators into the efficiency analysis framework and reduce the adverse effects of random errors on the estimation results, this paper combined the projection pursuit model with the stochastic frontier analysis method and proposed a translog stochastic frontier model considering undesirable outputs to analyse the multiple impacts of IURC on the EE of HTM. The results show that IURC has both a significant negative direct effect and a significant positive indirect effect on HTM's EE. Although IURC cannot directly promote EE, it has a positive impact on EE of HTM through its complementary effect with research and development investment. The results also confirm that the average EE of the whole country is only 0.346, while that of the eastern area is 0.595, and that of the central and western areas are 0.199 and 0.171, respectively. In general, there is much room for improvement in the EE of China's HTM. This study not only provides an improved SFA method for measuring EE, but also deepens research on the mechanism of the impact of IURC on HTM's EE.